A temporal study of Brazilian pregnant and postpartum women vulnerability for COVID-19: Characteristics, risk factors and outcomes - Natália S. Hojo-Souza; Daniel L. Guidoni; Cristiano M. Da Silva; Fernanda S.H. De Souza (Elsevier, 2022)
Summary: Background: During the COVID-19 second wave in Brazil, there has been a significant increase in the number of daily cases and deaths, including pregnant and postpartum women. We assess risk factors and outcomes for this priority group compared to the COVID-19 non-pregnant cohort in two epidemic waves. Methods: In this retrospective cohort study we evaluated data of hospitalized pregnant, postpartum, and nonpregnant women aged 15-44 years, between epidemiological weeks 2020-8 and 2021-15, who tested positive for SARS-CoV-2, retrieved from the Influenza Epidemiological Surveillance Information System maintained by Ministry of Health of Brazil. We analysed in-hospital case fatality rate, crude and adjusted risk ratios on different outcomes aiming to compare data in two waves. Findings: The study included pregnant women (n = 7,132), postpartum women (n = 2,405) and nonpregnant women (n = 76,278) hospitalized with COVID-19. Case fatality rates of pregnant women were lower in both waves compared to nonpregnant women, but higher among postpartum women. The risk for admission to the intensive care unit and invasive mechanical ventilation requirement in both waves was significantly higher among postpartum women compared to nonpregnant women. Cardiac disease, diabetes, obesity, and asthma were the most frequent underlying medical conditions in all patient groups. These comorbidities were significantly less frequent among pregnant women. Interpretation: Pregnant women with COVID-19 are at lower risk of poor outcome compared to nonpregnant women. On the other hand, postpartum women are at higher risk of adverse outcomes compared to pregnant and nonpregnant women, especially during the second wave. There was a significant increase in the in-hospital case fatality rate for all patient groups during the second wave of COVID-19. Funding: This study was financed in part by CAPES, CNPq, FAPEMIG and UFSJ.